Regeneration Status of an Oak Forest of Garhwal Himalaya - Rajwar, G. S.; Dhaulakhandi, Manoj; Kumar, Pramod (Indian Forester, 1999)
The density of seedlings and saplings, a measure of regeneration potential, was studied for ten forest sites with three stands each consisting of three elevational forest types : Quercus leucotrichophora-Pinus roxburghii (I800-2000m), Q. leucotrichophora (2000-220Om) and Q. floribunda (2200-2400m). In these forests the sapling density ranged from 2.64 to 7.73 saplings 25 m-2 , and seedling density 5.28 to 14.52 seedlings 25 m-2. On the basis of regeneration potential, Sites I to III were dominated by Q. floribunda, Sites IV to VIII and X by Q. leucotrichophora and Site IX by Pinus roxburghii. Most of the species were contiguously distributed. Only 88% of the tree species were recorded in seedling stage while sapling percentage is further reduced.